Creating and applying shared mental models in the operating room - Alister Wilson (Journal of Perioperative Nursing)
A shared mental model is a concept from high reliability environments, like aviation, to help teams develop collective understanding of how they will work together to safely accomplish their goals. Areas of high-risk health care like the operating room have adapted this concept to improve interdisciplinary teamwork and thus improve patient outcomes. Non-technical skills including communication, situational awareness, task management and leadership are employed to produce a functional shared mental model. Nurses play an important role in the change process as traditional hierarchical cultures, differing communication styles between doctors and nurses and an increasingly transient workforce are all challenges to the use of shared mental models in the operating theatre.